ANALISIS KETERSEDIAAN AIR UNTUK MENDUKUNG KETAHANAN PANGAN DI KABUPATEN MALAKA, NUSA TENGGARA TIMUR - Yulianingsani Yulianingsani; Haryono Putro (Rekayasa Sipil, 2019)
The growth of population causes growth in food needs. It cause availability of agricultural land getting smaller. The purpose of this study is to know the carrying capacity of agricultural land and analize water availability to support food security in Malaka. Malaka is an export-oriented food storage area in the border region (LPBE-WP). Based on the result of analisys, carrying capacity of agricultural land in Malaka on 2020-2024 is σ < 1. It means this region cannot afford food self-sufficiency, population beyond the limits of optimal (over populated). To achieve food self-sufficiency requires 12.516 hectares area of agricultural land. Based on water surplus graphics, the availability of water building infrastructure in Malaka cannot fulfill agricultural water needs. The volume of storage needed to fulfill agricultural water need is 86,201 million cubic meters.